ŽIŽEK DÜŞÜNCESİNDE ETİK, ÖZNE VE SİMGESEL DÜZEN İLİŞKİSİ. - ALAN SÜMER, Banu; ÜNLÜ, Havva (Felsefe ve Sosyal Bilimler Dergisi (FLSF))
This study examines the relationships between ethics, the subject, and the symbolic order in Žižek's thought. According to Žižek, ethics is defined by the individual's fidelity to their own desire and internal consistency, whereas morality is constrained by the norms governing relations with others; ethical action cannot be explained solely by social or rational criteria, emerging instead as an original and conflictual process. The subject is not a fixed entity but a divided, fragile, and multilayered structure; desire-objects and the subject's structural lack shape experiences and actions. The interplay between the symbolic and imaginary orders, together with the ruptures opened by the Real as their internal limit, renders visible the paradoxical structure of the subject and the conditions of ethical action. Reinterpreting analyses initiated in modern philosophy around the cogito and the notion of the absolute subject from a psychoanalytic perspective, Žižek offers a sustained reading of the subject's division and its relation to desire. Accordingly, ethics and the subject are conceived as processes of confronting the fissures of the Real that emerge at the limits of the symbolic order and of re-positioning oneself in relation to these structural impasses.